The Role of 'Village BA' in Enhancing Rural Sports Public Services: A Case Study of Rural Revitalization in Guizhou-China - Ye Biao (Ilmu Inovasi Nusantara, 2024)
Rural revitalization is a critical strategy for advancing rural development in China, with rural sports public services playing a key role in this process. This study focuses on the phenomenon of 'Village BA' in Guizhou, a local basketball competition that has gained significant popularity and is a key player in the rural revitalization process, largely due to the active community engagement. The study aims to analyze its success factors and impact on developing rural sports public services within the broader context of rural revitalization. Using empirical research methods, the study identifies several reasons behind the widespread appeal of 'Village BA,' including its deep cultural resonance and the crucial role of community engagement. Additionally, the study highlights the significant value that such events contribute to fostering competition and participation in rural sports services. The research also uncovers several challenges in the current 'Village BA' model. These include misalignment between the nature of sports and rural characteristics, inadequate sports infrastructure, insufficient safety measures, organizational management challenges, and limited service offerings. To address these issues, the study recommends developing more diverse and inclusive sports services, enhancing rural sports infrastructure, and creating an innovative 'sports+' development model that integrates sports with other sectors. Furthermore, it advocates for a diversified and coordinated supply of sports services to comprehensively promote the growth of rural sports public services. These strategies are intended to support the overall goal of rural revitalization by improving the quality of life and fostering community engagement through sports